IMPLICATIONS OF THE REGULATION OF SHARE TRANSFER IN STATE-OWNED ENTERPRISES AS STATE CAPITAL PARTICIPATION - Aristy, Tiara Putri; Sukarmi; Qurbani, Indah Dwi (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
State-owned enterprises (SOEs) are crucial to a country's economy. One of the ways SOEs obtain capital is through the transfer of shares. SOE share transfer arrangements are important in overseeing state capital in SOE companies. This study analyses the urgency of changing the share transfer arrangements in SOEs as state capital participation. This research uses normative research methods. The techniques used by researchers to obtain legal materials are document studies and literature studies. All legal materials successfully found and selected by researchers were inventoried, classified, and analyzed using systematic, grammatical and historical interpretation techniques. The results show that the ratio legis of the transfer of state-owned shares in BUMN as state equity participation in other BUMN in Government Regulation No. 72/2016 is to improve the performance of BUMN to be more efficient, effective, and profitable. The transfer of state-owned shares in SOEs as state equity participation in other SOEs aims to increase the efficiency of SOEs by optimizing existing resources, increase the effectiveness of SOEs by improving the quality of services to the public and increase the profitability of SOEs by increasing revenue and reducing costs.